Reactive power sharing control for islanded AC microgrid based on fuzzy adaptive compensation method. Issue 4 (18th December 2019) - Mi, Yang; Yan, Li; Cai, Hangyi; Fu, Yang; Tian, Shuxin; Jin, Chi
Abstract : Due to reactive power irrational sharing issue resulting from the mismatched line impedances and unbalanced local loads of the inverters, the hierarchical coordination control strategy based on fuzzy adaptive compensation is designed to improve the accuracy of the reactive power sharing in the islanded AC microgrid. Firstly, in the local controller, the total active power and the average reactive power are obtained by the initial power sharing stage and the secondary power sharing stage, respectively. Then, in the power balancing stage, the average reactive power as the input of the fuzzy control can be used to adaptively adjust the voltage reference value in real time, so the rational sharing of reactive power may be achieved by using the designed control strategy. Furthermore, based on the classification of load fluctuation, the coordinated operation strategy is designed to deal with reactive power sharing for different load fluctuation conditions. Noteworthy, only the low‐bandwidth synchronisation signal from the central controller is used to the hierarchical control strategy, which can maintain characteristic of plug‐and‐play in the microgrid. Simulation and experiment results are presented to validate the effectiveness of the proposed strategy.